El regreso de Abdalá - Torre, Carlos de la (2005)
This article explores the ambiguous relationships between populism and democracy by focusing on the rituals and discourses of Abdalá Bucaram´s return from exile. The article discusses the different meanings of the term “el pueblo”, the paradoxes of populist representation, and the populist meanings of democracy.